2013
DOI: 10.1002/2013gl058371
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial evolution of the Antarctic sea ice prior to the September 2012 record maximum extent

Abstract: On 24 September 2012 the Antarctic sea ice extent (SIE) reached a new annual daily maximum (ADM) for the satellite era of 19.72 × 106 km2. The largest positive SIE anomalies compared to the mean of all ADMs were found over the northern Amundsen Sea, off the coast of Wilkes Land, with smaller positive anomalies off the Dronning Maud Land coast (30°W to 30°E). The SIE at the ADM is significantly correlated with the extents for the previous 80 days, but the ice growth during the winter of 2012 was close to the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…The reduction in sea ice and increase in upper-ocean temperature for all the warming cases (Figs. 5a,c) is in contrast to recent observations showing increased ice production around Antarctica (Parkinson and Cavalieri 2012;Bintanja et al 2013;Turner et al 2013;Blunden et al 2014) and an ongoing cooling trend of Southern Ocean surface waters (e.g., Latif et al 2013;Fan et al 2014). Mechanisms driving these observed trends are poorly understood.…”
Section: A Surface and Sea Ice Responsementioning
confidence: 70%
“…The reduction in sea ice and increase in upper-ocean temperature for all the warming cases (Figs. 5a,c) is in contrast to recent observations showing increased ice production around Antarctica (Parkinson and Cavalieri 2012;Bintanja et al 2013;Turner et al 2013;Blunden et al 2014) and an ongoing cooling trend of Southern Ocean surface waters (e.g., Latif et al 2013;Fan et al 2014). Mechanisms driving these observed trends are poorly understood.…”
Section: A Surface and Sea Ice Responsementioning
confidence: 70%
“…The positive trends in Antarctic sea ice extent are currently poorly understood and are at odds with climate model forecasts that suggest the sea ice should be declining in response to increasing green- house gases and stratospheric ozone depletion (e.g., Bitz and Polvani, 2012;Sigmond and Fyfe, 2010). However, several modeling studies, such as those used in the phase 5 Coupled Model Intercomparison Project (CMIP5), have suggested that the sea ice increase over the last 36 years remains within the range of intrinsic of internal variability (e.g., Bitz and Polvani, 2012;Turner et al, 2013;Mahlstein et al, 2013;Polvani and Smith, 2013;Swart and Fyfe, 2013). Earlier satellite data from the 1960s and 1970s and data from ship observations suggest periods of high and low sea ice extent and thus high natural variability (Meier et al, 2013b;Gallaher et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Studies point to anomalous short-term wind patterns that both grow and spread out the ice, related to the strength of the Amundsen Sea low pressure (e.g., Turner et al, 2013;Reid et al, 2015;Holland and Kwok, 2012). Other studies suggest meltwater from the underside of floating ice surrounding the continent has risen to the surface and contributed to a slight freshening of the surface ocean (e.g., Bintanja et al, 2013).…”
mentioning
confidence: 99%
“…The positive sea ice trend might be in part the result of stratospheric ozone depletion that has caused a deepening of the lows in the West Antarctic region (Turner et al 2009;Sigmond and Fyfe 2010;Turner et al 2015). The atmospheric conditions over the area between the Antarctic Peninsula and the Ross Sea are controlled primarily by the Amundsen Sea low (Turner et al 2016), which gives rise to the climatological southerly winds over the Ross and Amundsen Seas.…”
Section: Introductionmentioning
confidence: 99%
“…The atmospheric conditions over the area between the Antarctic Peninsula and the Ross Sea are controlled primarily by the Amundsen Sea low (Turner et al 2016), which gives rise to the climatological southerly winds over the Ross and Amundsen Seas. The interannual variability of the sea ice extent in the Ross Sea sector has been significantly correlated with the strength of the southerly winds over the Ross Sea and the depth of the Amundsen Sea low (Turner et al 2016).…”
Section: Introductionmentioning
confidence: 99%